THE ENHANCEMENT OF COMMUNICATION SKILL AND PREDICTION SKILL IN COLLOIDAL CONCEPT BY PROBLEM SOLVING LEARNING - Agita Dzulhajh Anggraini; Noor Fadiawati; Chansyanah Diawati (Universitas Lampung, 2012)
Accuracy educators in selecting and implementing learning models influence students' science process skills. Models of learning that can be applied to improve science process skills and tend constructivist among athers learning model of problem solving. This research was conducted to describe the effectiveness of the learning model of problem solving in improving communication skills and prediction skills. Subjects in this research were students of high school YP Unila Bandar Lampung Even semester of classes XI IPA4School Year 2011-2012. This research used a pre-experimental method with One Group Pretest-Posttest Design. The effectiveness of the learning model of problem solving was measured by differences in understanding of the beginning and end of the students' understanding shown by the mean n-Gain. Based on the results of this research, average value of n-Gain for communication skills is 0.63 and the average value of n-Gain for prediction skills is 0.40. This shows that (1) a model of problem solving is effective in improving the communication skills in the medium category (2) a model of problem solving is effective in improving prediction skills in the medium category.Ketepatan pendidik dalam memilih dan menerapkan model pembelajaran berpengaruh terhadap keterampilan proses sains siswa. Model pembelajaran yang dapat diaplikasikan untuk meningkatkan keterampilan proses sains siswa dan mengacu pada konstruktivisme adalah model pembelajaran problem solving. Penelitian yang bertujuan untuk mendeskripsikan efektivitas model pembelajaran problem solving dalam meningkatkan keterampilan berkomunikasi dan keterampilan memprediksi telah dilakukan. Subjek dalam penelitian ini adalah siswa SMA kelas XI IPA4 YP Unila Bandar Lampung tahun ajaran 2011-2012. Penelitian ini menggunakan metode preksperimen dengan desain One Group Pretest-Posttest. Efektivitas model pembelajaran problem solving diukur dengan membandingkan pemahaman siswa sebelum dan setelah pembelajaran, dimana pemahaman diindikasikan dari rerata nilai n-Gain. Berdasarkan hasil penelitian, rerata nilai n-G untuk keterampilan berkomunikasi sebesar 0,63 dan untuk keterampilan memprediksi sebesar 0,40. Hal ini menunjukkan bahwa model problem solving efektif dalam meningkatkan keterampilan berkomunikasi dan keterampilan memprediksi dalam rentang menengah.Kata kunci: keterampilan berkomunikasi, keterampilan memprediksi, problem solving